Development of Socio-Cultural Competence of the Government Employees at the State Civil Service and Human Resource Development Agency of Biak Numfor Regency Papua Province - Sudarman, Fatmawada (Research and Development Agency Ministry of Home Affairs, 2018)
The low educational level of the government employees at the State Civil Service and Human Resources Development Agency of Biak Numfor Regency in Papua Province affects the quality of public services which was far from the society’s expectations. The development of competence that has been given so far had not been able to change the primal aspects of the government employees. Therefore, the development of competence provided must touch the large and varied cultural diversity that leads to the improvement of knowledge, capability, and skills to generate better performance and services. This study aims to analyze the development of the government employees’ competence at the State Civil Service and Human Resources Development Agency of Biak Numfor Regency, Papua Province. The method used in this research was descriptive research with a qualitative approach. Primary data was collected through observation, interviews and Focus Group Discussion (FGD); the respondents were the government employees in the State Civil Service and Human Resource Development Agency of Biak Numfor Regency, Papua Province. Secondary data were obtained through documentation studies. The data were analyzed using interactive models. The results showed that the process of developing the socio-cultural competence of the government employees in the State Civil Service and Human Resource Development Agency of Biak Numfor Regency, Papua Province was through: 1) BIMTA (Mental and Spiritual Guidance), 2) JUMAT BELI (Friday clean environment program), 3) Leadership Advice through meetings and assembly, 4) Education and Training, which still need to be improved such as providing special program through education and training, seminars, courses, and upgrading related to socio-cultural competence to encourage them to have national insights with a pluralistic society in terms of religion, ethnicity, culture, and able to adapt and communicate effectively, empathetically, and politely among employees and the society.